In vitro Activity of Fosfomycin against Multidrug-Resistant Urinary and Nonurinary Gram-Negative Isolates - Behera, Bijayini (Indian J Crit Care Med, 2018)
BACKGROUND: The era of multidrug-resistant (MDR) Gram-negative bacilli (GNB) has renewed interest in fosfomycin. AIM: The present study evaluated the in vitro activity of fosfomycin against MDR urinary and nonurinary GNB isolates. MATERIALS AND METHODS: Fosfomycin susceptibility was carried out by agar dilution for a total of 279 (142 from urine and 137 from other samples) MDR-GNB. Disk diffusion was done for urinary isolates only. RESULTS: Urinary tract isolates had a high degree of susceptibility to fosfomycin (overall susceptibility, 90.8%), whereas only 42.9% of nonurinary isolates retained susceptibility to the drug. Percentage susceptibility rates for urinary and nonurinary isolates of Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter spp. were 99%, 91.3%, 66%, 0% and 62%, 44.4%, 32%, 11%, respectively. CONCLUSION: Fosfomycin showed excellent in vitro activity for uropathogens. Large-scale evaluation of fosfomycin against MDR systemic isolates is required to evaluate its therapeutic efficacy.